2022
DOI: 10.20473/fmi.v58i1.31423
|View full text |Cite
|
Sign up to set email alerts
|

Acute Diarrhea Patients among Children Under Five Hospitalized in a Tertiary Hospital in East Java, Indonesia

Abstract: Highlight:The characteristics of acute diarrhea patients among chidren in Tertiary Hospital In East Java was evaluated.The highest incidence of diarrhea was found in the 0-24 months age group, good nutritional status, male sex, and hospitalized in less than 5 days.Mild-moderate dehydration, intravenous rehydration treated, anemia, hyponatremia, and metabolic acidosis were mostly founded. Abstract:Diarrhea is the second leading cause of morbidity and mortality in children under five years of age in Indonesia af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…The findings of this study were comparable to those of a study by Adiba et al (2022) at a tertiary hospital in Surabaya, which revealed that mild and moderate were the most prevalent degrees of dehydration. However, the most common method of rehydration used was intravenous rehydration.…”
Section: Resultssupporting
confidence: 87%
“…The findings of this study were comparable to those of a study by Adiba et al (2022) at a tertiary hospital in Surabaya, which revealed that mild and moderate were the most prevalent degrees of dehydration. However, the most common method of rehydration used was intravenous rehydration.…”
Section: Resultssupporting
confidence: 87%
“…1 Diarrhea is classified as osmotic (due to lactose intolerance and toxin), secretory (due to cholera infection, E.coli, Shigella species), or inflammatory (due to enterotoxin). 3 The most prevalent cause of pediatric diarrhea is rotavirus infection, particularly in children aged 3-24 months. Vomiting, fever, and diarrhea are all symptoms of rotavirus infection.…”
Section: Discussionmentioning
confidence: 99%
“…Hyponatremia (41%), hypokalemia (38.6%), hypernatremia (11.4%), and hyperkalemia (9%) were the most prevalent electrolyte abnormalities. 3 A study in India by Takia et al showed the incidence of metabolic acidosis in acute diarrhea with severe dehydration was 13% of the total 929 cases. 8 While another study by Zain et al in 2020 in 280 cases, found the incidence of metabolic acidosis was 29.5% of the total cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infants commonly have hypertrophic pyloric stenosis (HPS) (1). HPS occurs in 2 to 5 per 1000 live births (2).…”
Section: Introductionmentioning
confidence: 99%